Women and the Criminal Justice System Failing Victims and Offenders? (Springer International Publishing, 2018)
Bringing together academics and professionals, this edited collection considers key issues in current criminal justice policy and practice related specifically to women to answer the important question: are women being failed by the criminal justice system? In a landscape where women's involvement in the criminal justice system still tends to be ignored or lost in discussions about men, contributors place special emphasis on women as both victims and offenders. The chapters cover a wide range of topics relating to women and crime, including: violent and sexual victimisation, violent offending, sentencing and punishment, and rape myths. Since the peak of feminist criminal justice scholarship in the 1990s, the place of women in the criminal justice system has arguably slipped down the agenda and the authors of this collection draw on original research to make the compelling case for a swift remedy to this. Drawing on recent academic studies and professional experience to set an agenda for future research - as well as legal and policy reform - this book injects new life into the dialogue surrounding women and the criminal justice system. Innovative and timely, this collection of essays holds broad appeal to academics and practitioners, as well as students of criminology, criminal justice and law, and all those with an interest in feminism, justice, and inequality.